Control Algorithm For Optimal Spare Part Inventory - Yek, Siew Huat (2005)
This study explores the possibility of getting a pragmatic solution for a spare parts management issue where 'too little" or "too many" come into picture. A company faces challenges in either scenario, and sensible solution which strike the balance between "too little" and "too many" is crucial, and it is the focus of this study in this thesis.